EXPANDING THE TECHNOLOGICAL CAPABILITIES OF FLAT TWO NEEDLE KNITTING MACHINES FOR RECEIVING TWO-LAYER KNITTED FABRICS IN A NEW STRUCTURE - J. Z. Borotov; K. M. Xoliqov; G.X.Gulyaeva; M. M. Mukimov; N. N. Yoqubjanov (European Science Publishing, 2023)
Using the technological capabilities of double-bed flat knitting machines, the technology for producing double-layer knitted fabrics of a new structure, made by arranging the needles in interlock positions, has been studied.
Keywords: interlock, needle, double-layer, knitting, technology.